1981
DOI: 10.3758/bf03333675
|View full text |Cite
|
Sign up to set email alerts
|

Self-reference in facial recognition

Abstract: Subjects made decisions about facial photographs and were tested later for recognition memory of the pictures. The study decisions involved judgments about abstract personality traits (e.g., friendliness) or physical features (e.g., lip thickness) relative to either self-comparisons or some nonself standard. The expected abstract-physical feature difference emerged, but there was no evidence for a self-other difference for either type of feature. A molar self-reference task specifying no particular attribute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Nevertheless, despite the disparity between nonverbal and verbal memory for faces, a number of studies have demonstrated that describing a face can either facilitate or interfere with subsequent visual recognition. Verbal facilitation has been reproduced in a number of studies (e.g., Bloom & Mudd, 1991;Bower & Karlin, 1974;Mueller, Courtois, & Bailis, 1981). Verbal interference has also been observed, albeit less frequently (for a review, see Schooler, 2002).…”
mentioning
confidence: 92%
“…Nevertheless, despite the disparity between nonverbal and verbal memory for faces, a number of studies have demonstrated that describing a face can either facilitate or interfere with subsequent visual recognition. Verbal facilitation has been reproduced in a number of studies (e.g., Bloom & Mudd, 1991;Bower & Karlin, 1974;Mueller, Courtois, & Bailis, 1981). Verbal interference has also been observed, albeit less frequently (for a review, see Schooler, 2002).…”
mentioning
confidence: 92%
“…eral studies have shown that making trait judgments (e.g., niceness) to unfamiliar faces at encoding leads to better recognition than does making physical judgments, such as those of gender (see, e.g., Bower & Karlin, 1974;Mueller et al, 1981;Patterson & Baddeley, 1977). Accounts of the levels-of-processing effect can be broadly separated into those that emphasize either visual or semantic processing.…”
mentioning
confidence: 99%
“…We are aware of another study in which the ideal self was used in an orienting task, but because the stimuli were facial photographs, it is hard to integrate this study into the large body of self-reference work done with trait adjectives (Mueller, Nicodemus, & Ross, 1981). It is worth noting, however, that face memory for real-self and idealself tasks was equivalent, in accord with Grove and Mueller (1988).…”
Section: Notesmentioning
confidence: 74%